Perancangan Sistem Pakar Gejala Penyakit Pada Burung dan Kucing Menggunakan Metode Forward Chaining Berbasis Android - Rahmi Imanda; Damar Kharisma Fauziyyah (Jurnal Teknik Informatika dan Komputer, 2022)
This study discusses the problems experienced by pet owners, especially cats and birds in dealing with diseases experienced by their pets. Based on the results of the questionnaires that have been conducted, as many as 74.3% of pet owners have minimal knowledge about what types of diseases can attack their pets (cats and birds), 80% of the distance traveled to the vet clinic is quite far, 60% of the existing veterinarians are still relatively minimal, and pet owners have their own busy lives and activities. This study aims to create an expert system in the form of an android-based application, which can assist pet owners in obtaining information about the results of disease symptoms in pets, what kind of treatment can be given, drug suggestions for the disease. The method for tracing the solution used is the Forward Chainig method, where the analysis is carried out after the information is given to then produce conclusions in the form of the name of the disease. The kar system application is made using the Java and PHP programming languages. The expert system application created in this study can help pet owners, especially cats and birds, in getting information about the symptoms of diseases that attack their pets. This is based on the results of testing the beta test results of all the features in the application running well and a success rate of 100%, and based on the results of the effectiveness test of the acceptance of this expert system application, it is very good at 89.35%.